2017
DOI: 10.1093/neuros/nyw086
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation vs Antiplatelet Treatment in Patients with Carotid and Vertebral Artery Dissection: A Study of 370 Patients and Literature Review

Abstract: The rate of new or recurrent events is similar with antiplatelet and anticoagulation treatment in treating intracranial and extracranial carotid and vertebral artery dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 28 publications
0
37
0
1
Order By: Relevance
“…Stroke rate among BCVI patients has a large variation from 1% up to 53.8%. The majority of these strokes were already in progress when the patient has been admitted to a hospital [5,10,12,17,26,30,39,40,42].…”
Section: This Article Is Part Of the Topical Collection On Brain Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke rate among BCVI patients has a large variation from 1% up to 53.8%. The majority of these strokes were already in progress when the patient has been admitted to a hospital [5,10,12,17,26,30,39,40,42].…”
Section: This Article Is Part Of the Topical Collection On Brain Traumamentioning
confidence: 99%
“…Correlating injuries and predisposing conditions to CAI are facial injuries, diffuse axonal injury (DAI), Glasgow Coma Scale (GCS) < 6, and road traffic collisions [34,40]. In terms of patient outcome, CAI seem to be worse than VAI [10].…”
Section: Introductionmentioning
confidence: 99%
“…There was also no difference between intracranial and extracranial dissections. The rate of unfavourable clinical outcome (Modified Rankin Score 3–6) did not differ between patients on different courses of treatment 29. Multiple meta-analyses of non-randomised studies of carotid and VADs showed no difference in recurrent stroke, complications or mortality comparing anticoagulation with antiplatelet therapy 30 31.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, he was started on anti-platelet therapy with Aspirin 325 mg. Studies have demonstrated similar efficacy between anti-platelet agents and anticoagulants in the treatment of vertebral artery dissections. Although hemorrhagic complications have been reported, the association between these complications and antithrombotic use is not proven [13][14][15].…”
Section: Discussionmentioning
confidence: 99%